2017
DOI: 10.1177/1049732317746381
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Keep Immigrant Travelers Healthy? Health Challenges Experienced by Canadian South Asian Travelers Visiting Friends and Relatives

Abstract: Immigrant travelers who visit friends and relatives (VFR travelers) experience substantially higher rates of travel-related infections than other travelers, in part due to low uptake of pretravel health advice. While barriers to accessing advice have been identified, better characterization is needed to inform targeted interventions. We sought to understand how South Asian VFR travelers perceived and responded to travel-related health risks by conducting group interviews with 32 adult travelers from an ethnocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Still, most participants reported maintaining vigilance against mosquitoes, even if these practices were more stringent than those used by their hosts. To overcome the barriers to the use of particularly intrusive mosquito bite, preventive measures such as bed-nets, an especially strong motivator for use was required, such as to protect children 24 or a particularly healthconscious traveller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, most participants reported maintaining vigilance against mosquitoes, even if these practices were more stringent than those used by their hosts. To overcome the barriers to the use of particularly intrusive mosquito bite, preventive measures such as bed-nets, an especially strong motivator for use was required, such as to protect children 24 or a particularly healthconscious traveller.…”
Section: Discussionmentioning
confidence: 99%
“…25 Future community-based programming must address the unique barriers VFR travellers face and take into consideration measuring the impacts of social and behavioural motivators which influence decision-making before and during travel. 24 Further, comparing experiences of VFRs who contract malaria and those who do not could shed light on barriers that most strongly correlate with disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although public funding of pretravel health services for VFR travelers might eliminate cost-related barriers, other factors need to be considered and addressed to effectively reduce disease burden in this population. Qualitative studies have found that social contexts and relationships are mediators of the choices and behaviors of VFR travelers ( 20 , 22 ). Unlike business or leisure travelers, VFR travelers often stay with family members when visiting and are part of collectivist cultures that place a strong emphasis on acting in the best interest of the family rather than an individual member.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike business or leisure travelers, VFR travelers often stay with family members when visiting and are part of collectivist cultures that place a strong emphasis on acting in the best interest of the family rather than an individual member. These cultural value systems might influence VFR travelers to make decisions to maintain family harmony at the expense of personal health and to go against medical or public health advice to be able to fully participate in cultural activities or rituals that are of value to them ( 20 ). They also might need to travel in rushed circumstances to attend to a sick or dying relative.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly described as a single population, VFR traveler subgroups may vary in their adherence to malaria prevention and in their interactions with health care systems [10,12,27]. Studies of VFRs residing in other countries and engaging with the health care systems in those countries have shown that differences in malaria prevention behaviors are broad, and the heterogeneity of experiences among immigrant VFRs should not be understated [36][37][38].…”
Section: The Heterogeneity Of the Vfr Populationmentioning
confidence: 99%